ANALISIS MATEMATIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN MS GLOW - Annisa Nur Afifah Kusuma Sayekti; A’yunin Sofro (LPPM Universitas Bina Bangsa, 2024)
In this increasingly advanced era, beauty products are increasing. Not only women, men also enjoy the development of this beauty product. One beauty brand that keeps up with current developments is the MS Glow brand. The MS Glow brand not only offers types of skincare that are suitable for men and women. This brand offers skincare that is licensed by BPOM and Halal MUI. Even though this brand is well known to the general public, it is necessary to identify the factors that influence customers' decisions in purchasing MS Glow products. This can help increase the popularity of MS Glow products. The cultural factor used in this research is the attitude of wanting to own what other people have or just following trends in the surrounding area. From this factor it can be concluded that the cultural factor is a